Platinum on Oxidized Graphene Sheets: A Bifunctional Electrocatalyst for Hydrogen Oxidation Reaction and Methanol Oxidation Reaction. (1st July 2022) - Parkash, Anand; Kumar, Raj; Abbasi, Irfan Ahmed; Aurangzeb, Junejo; Inam, Muhammad Ali; Larik, Rimsha; Khan, Rizwan
Abstract : Pt/Graphene has been prepared by polyol method using pre-functionalized graphene and Pt salt solution, hexachloroplatinic acid. Electrochemical studies of the Pt supported onto graphene showed improved performance for Hydrogen Oxidation Reaction (HOR) and Methanol Oxidation Reaction (MOR) compared to state-of-the-art Pt/C catalysts. A thermal treatment (Ar/H2, 100 °C, 3 h) applied to the catalysts improved the catalytic activity and stability of the Pt/Graphene catalyst showing an electrochemical surface area of 58 m 2 .g −1 and stability was found 3-fold higher than the Pt/C conventional catalyst. After 4, 000 cycles, the cyclic voltammetry measurements showed that the Pt/Graphene catalyst lost only 20% of the Pt initial ECSA, whereas the degradations of Pt /C catalyst were quite high, showing 65% loss. The Pt/Graphene catalyst also exhibited higher performance in the methanol electrooxidation for the promotion of C–H breaking and COad tolerance and good stability. Due to the homogenous distribution of Pt particles on the graphene and the availability of these surfaces for hydrogen adsorption and desorption processes, Pt/Graphene was reported to have 2-fold greater electrochemical performance towards methanol oxidation than Pt/C. Additionally, the findings contribute to an improved mass movement in the catalyst layer. According to this research, the oxygenation groups and graphitization have a dual role in catalytic activity.